PENGARUH SISTEM ADMINISTRASI PERPAJAKAN MODERN TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI - Septriliani, Lia; Ismatullah, Ismet (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2021)
This research aims to find out the Influence of the Modern Tax Administration System on Personal Taxpayer Compliance. The type of research used is quantitative with an associative approach. The variables used in this study are the Modern Tax Administration System and Taxpayer Compliance. The population in this study is all Private Person Taxpayers registered with The Tax Office of Pratama Sukabumi, while the sample in this study is as many as 400 respondents. The sampling technique used is random sampling. The analysis used is Partial Least Square (PLS) with Smart PLS version 6.0. The results of this study show that the ꞵ= 0.676 coefficient and signification value of 0.001 This indicates that the significance of the Modern Tax Administration System is 0.001<0.05 which means there is a significant influence between the Modern Tax Administration System on Personal Taxpayer Compliance. Keywords: Modern Tax Administration System, Taxpayer Compliance of private persons